Edge effects and landscape matrix use by a small mammal community in fragments of semideciduous submontane forest in Mato Grosso, Brazil - Santos-Filho,M. (2008)
A community of small mammals was studied in seasonal semideciduous submontane forest in the state of Mato Grosso, Brazil. This study evaluated the use of edge and matrix pasture, by different small mammal species. Overall, 31 areas were studied, with a total sampling effort of 33,800 trap x nights. Only seven of the 25 species captured in the study sites were able to use the pasture matrix; we classified these species as generalists. Fourteen species were found to be intermediate in habits, being able to use forest edges. We found only four species habitat specialists, occurring only on transect lines in the interior of the fragment, at least 150 m from the edge. Transects located in the pasture matrix and 50 m from the edge had significantly lower species richness and abundance than transects located in the fragment edge or in the interior of the fragment. All transects located within the fragment had similar species richness and abundance, but transects located 50 m from the edge had slightly lower, but non-significant, species richness than transects located 100 m apart from edges. Rarefaction curves demonstrated that only medium-sized fragments (100 300 ha) reached an asymptote of species accumulation. The other areas require further sampling, or more sampling transect, before species accumulation curves stabilize, due to a continued increase in species number.